The Marriage of Indigenous Peoples of Lampung Saibatin in the Perspective of Islamic Law and Tafsir of Gender Verses - Baihaqi, Yusuf; Kasdi, Abdurrohman; Farida, Umma; Maraliza, Helma (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2022)
The indigenous people of Lampung Saibatin are adherents of the Islamic religion. However, in the marriage tradition, there are still several gender-biased customs that are not in harmony or even contrary to the values of Islamic teachings. The formulation of the problem in this article is how is the level of compatibility between the marriages of the Lampung Saibatin indigenous people and the teachings of Islam they believe? The purpose of this article is to describe the concept of marriage in the Qur'an and marriage customs in the Lampung Saibatin indigenous community and their compatibility with Islamic teachings through the study of gender verses in the Qur'an. The method used is qualitative, with a sociological approach. The focus of this study is to present an interpretation of the gender verse, then relate it to what is practiced by the Lampung Saibatin indigenous people in their marriage customs. The results of the study show: First, there is still a gap between the teachings adopted by the Lampung Saibatin indigenous people and their marriage customs. Second, gender inequality is still often practiced in the marriage customs of the Lampung Saibatin indigenous people. Third, referring to the values of religious teachings adopted by the indigenous people of Lampung Saibatin, it is a solution to the gender injustice in their marriage customs. Fourth, the local wisdom in the marriage of the Lampung Saibatin indigenous people in ending conflicts between families and minimizing the divorce rate. The results of this study contribute to explaining the marriage customs in the internal Lampung Saibatin indigenous community and enlightening the external parties that it is not always what is traditions by a Muslim community is a representation of their religious teachings. Besides, not all marriage practices in the traditional Lampung Saibatin community are poor because there are the values of local wisdom in their marriage customs.